The Challenges of BSHM Student on Virtual Learning at Bestlink College of the Philippines S.Y. 2021-2022: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The hard lockdown in the Philippines began in March 2020 due to the coronavirus disease (COVID-19) outbreak. For the safety of the students and teachers, the government and the Commission on Higher Education (CHED) suspended face-to-face classes and recommended virtual learning. Virtual learning is an effective way to continue education during the pandemic. Still, it poses a big challenge for teachers, students, and parents who need help to afford the necessary equipment and internet connection. This study aims to evaluate BSHM students' difficulties with virtual learning and identify its effects.  The researchers used the quantitative-descriptive research method and gathered data from 50 BSHM students at Bestlink College of the Philippines using an online questionnaire in Google Forms. The survey revealed that all BSHM students faced the same challenges, including distraction at home, poor internet connection, financial difficulties, unexpected power outages, and technical problems. These challenges caused anxiety, depression, and stress among the students. Despite the impact of these challenges, students preferred to set achievable goals, stay connected, have intrinsic motivation, and develop time management to acquire knowledge. Based on this research, it is important to investigate and determine the challenges faced by students on virtual learning, the effects of these challenges on students, and how they can help themselves despite the challenges they have experienced. The researchers recommend that institutions provide load support to access virtual classes, improve internet connection, and provide technical support to students. Additionally, institutions should conduct orientation meetings and training sessions to boost students' problem-solving, professionalism, and human relations skills.
Keywords: BSHM; Challenges; COVID 19; Virtual Learning